Digital Campaign Strategy: TikTok Content Analysis of Candidate No. 1 Eri Armuji on Voters' Preferences in the 2024 Surabaya regional election - Saiful Hasan; Ainur Rofiq (PT Pro Panoramic Solution, 2025)
The use of social media in political campaigns is increasing, especially on video-based platforms like TikTok. In the 2024 Surabaya Election, candidate pair (Paslon) number 1, Eri Armuji, utilized TikTok as one of their digital campaign strategies. This study examines the influence of TikTok campaign content from Paslon number 1 on voter preferences in the 2024 Surabaya Election. It examines how content strategy influences voter perceptions and decisions, employing a qualitative approach and assessing the effectiveness of political communication through agenda-setting and the Elaboration Likelihood Model (ELM). Data was collected through content analysis of a TikTok campaign video by the Eri-Armuji team. The findings indicated that emotional content and local issues had a stronger influence on voter preferences than just campaign promises. Additionally, engagement via likes, comments, and shares boosted the candidates' popularity among young voters.. This study concludes that the digital campaign strategy through Tiktok can be an effective tool in influencing voter preferences, especially by utilizing relevant narratives and readily accepted by digital audiences. This study also emphasized the importance of adaptation of political communication strategies in the digital era to increase the effectiveness of the campaign